Difficulties the Conservative Treatment of Crohn’s Disease Complicated by Autoimmune Hemophilia A - E. L. Belyaeva; O. I. Filippova; A. V. Koloskov; A. A. Naydenov; F. D. Albegova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present a clinical case describing the management of a patient with Crohn’s disease complicated by recurrent intestinal bleeding and autoimmune hemophilia A.General provisions: A 21-year-old patient was admitted to St. Petersburg City Hospital No. 26 and diagnosed with Crohn’s disease with the lesions of the ileum, sigmoid and rectum in inflammatory form and continuously recurrent course. Upon admission, the patient demonstrated an elongated activated partial thromboplastin time (aPTT). In this connection, the levels of VIII (FVIII) and IX (FIX) coagulation factors and the content of von Willebrand factor antigen were determined. A study was conducted to the antibodies to these factors connecting von Willebrand factor capabilities with type I and III collagen. A 7 % decrease in the FVIII level and the presence of FVIII antibodies were detected. The patient was diagnosed with autoimmune hemophilia A. On August 14 in 2019, pulse therapy with methylprednisolone of 1000 mg per day by intravenous drip was started. After the first infusion, the aPTT index returned to normal and comprised 30 seconds, while the FVIII activity increased to 255 %.Conclusion. The presented clinical case demonstrates the importance of timely diagnosis and treatment of acquired coagulopathy. Acquired hemophilia A can be a life-threatening condition. When acquired coagulopathy develops in a patient with bleeding against the background of an inflammatory bowel disease, it aggravates the course of the disease and worsens the prognosis.